Consolation Miracle - Davidson, Chad, 1970- (Book collections on Project MUSE., 2003)
Consolation Miracle is a book of visceral, image-driven poems that search for the miraculous in the seemingly ordinary. This collection fashions art out of artless objects as a consolation, or perhaps compensation, for their smallness. Yawns and pears, cockroaches and crows resonate against historically conflated backdrops, while our own hands seem suddenly strange as they hide themselves in our pockets, balance a burning cigarette between two fingers, or grip the gun that shot Lincoln. Other poems address the destruction of empire, the end of old Hollywood, and the hyperbo.